2015
DOI: 10.1002/chem.201500809
|View full text |Cite
|
Sign up to set email alerts
|

Powerful Bispyridinylidene Organic Reducing Agents with Iminophosphorano π‐Donor Substituents

Abstract: Four members of a new family of powerful bispyridinylidene organic reducing agents have been prepared, which exploit iminophosphorano (-N=PR3; R = Ph, Cy) π-donor substituents. Electrochemical studies show exceptionally high oxidation potentials, ranging from 1.30 to 1.51 V versus SCE. These new reductants were shown to effectively convert 1-bromonaphthalene to naphthalene under mild reaction conditions. From the redox potentials, substituent constants (σp(+)) for the iminophosphorano groups Ph3P=N- (-1.82) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 60 publications
3
35
0
Order By: Relevance
“…Rhodium complexes bearing phosphinimine donors as part of am onoanionic R NNNl igand set, ( R NNN = 2,5-[R 2 P = N(4-iPrC 6 H 4 )] 2 N(C 4 H 2 ) À ,R= Ph, iPr) have recently been shownt o have ap ropensity to enact cooperative bond activation of H 2 and CO. [12] The ylidic nature of the PÀNb ond results in strongly basic Nd onors capable of stabilizing electrophilicm etals and main group functionalities. [13] Following the recognition that silylenes are defined by the pronouncedL ewis acidity of the Si atom, [8] precursor Rh silyl hydride complexes bearing a strongly-donating ligand set were targeted. To luene solutions of ( iPr NNN)Rh(COE)( 1-COE) and 1equivalent of PhSiRH 2 (R = H, Ph) were stirred for 1hour at ambient temperature leading to SiÀHo xidative addition, alongw ith concomitantl oss of COE (Scheme 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rhodium complexes bearing phosphinimine donors as part of am onoanionic R NNNl igand set, ( R NNN = 2,5-[R 2 P = N(4-iPrC 6 H 4 )] 2 N(C 4 H 2 ) À ,R= Ph, iPr) have recently been shownt o have ap ropensity to enact cooperative bond activation of H 2 and CO. [12] The ylidic nature of the PÀNb ond results in strongly basic Nd onors capable of stabilizing electrophilicm etals and main group functionalities. [13] Following the recognition that silylenes are defined by the pronouncedL ewis acidity of the Si atom, [8] precursor Rh silyl hydride complexes bearing a strongly-donating ligand set were targeted. To luene solutions of ( iPr NNN)Rh(COE)( 1-COE) and 1equivalent of PhSiRH 2 (R = H, Ph) were stirred for 1hour at ambient temperature leading to SiÀHo xidative addition, alongw ith concomitantl oss of COE (Scheme 2).…”
mentioning
confidence: 99%
“…While Rh!CO backbonding interactions of p-symmetry were observed, our DFT analyses do not support the presence of substantial Rh!Si p bonding, such as those reported previously for iridiums ilylenes. [13,14] Notably,D jukic and co-workers found that coordinationo fT HF to an Ir = SiHPh moietyr esulted in a3 0% reduction of the p characteri nt he IrÀSi interaction. [16] We therefore reason that the stronger s-donora bilities of the phosphinimine in 3,c ompared to THF,m ay account for the diminished double bond character in this system.Acomparisono ft he natural atomic charge on Si in 3-SiHPh, with that in the base-free (PNP)Ir(H) = SiHMes (PNP = [N(2-PiPr 2 -4-Me-C 6 H 3 ) 2 ] À ), reported by Tilley, [10] indicated similar values (+ 1.19 cf.…”
mentioning
confidence: 99%
“…This assignment is indirectly supported by theoretical studies by Clennan et al who found that the Z-anti conformation of 4c to be the most stable isomer by 1.59 kcal/mol over the lowest energy E conformation, 22 and by the fact that NOE-type NMR experiments validated the E isomer as the minor isomer for related iminophosphorano-substituted bispyridinylidenes. 20,21 Unlike derivatives of 6, which showed substantial double bond character of the N-C pyridyl bond, as evidenced by two distinct methyl groups for the N(CH 3 ) 2 substituents by 13 C and 1 H NMR spectroscopy, derivatives of 4 showed only one resonance for the same group, indicating free rotation of the N-C bond at room temperature. This indicates that the exocyclic amino group exerts a stronger π-donating effect in the oxidized species 6 than in neutral 4, suggesting the importance of the quinoid-type form 6', despite the fact that this would decrease the aromatic character of the ring.…”
Section: Introductionmentioning
confidence: 98%
“…11,12 More recently, we have been able to isolate some iminophosphorano-substituted bispyridinylidenes, which are even more powerful reductants. 20,21 The availability of isolable reducing agents, free from by-products or excess base from their in situ generation, can be beneficial in increasing the utility of these reagents. Therefore, in order to facilitate the adoption of bispyridinylidenes as accessible and synthetically valuable reducing agents, we were interested in preparing and isolating a series of these compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation